Low-carbon competitiveness in Asia - Sugandha Srivastav; Sam Fankhauser; Alex Kazaglis (Economies, 2018)
Environmental degradation and the risks from climate change have strengthened the need for cleaner forms of economic growth. Using patent, trade and output data, we measure the current size of Asia's low-carbon economy and assess its competitiveness across key sectors. We look at three success factors for low-carbon competitiveness at the sector level: the ability to convert to low-carbon products and processes (measured by a specialization in low-carbon innovation), the ability to gain and maintain market share (measured by existing comparative advantages) and a favorable starting point (measured by current output and scale). Using this framework, we identify the 'climate change mitigation technologies' that Asian countries specialize in and can potentially scale up. The analysis shows that Asia's top low-carbon economies are Japan, South Korea and China. The sectors in which Asia is particularly well placed to be globally competitive include efficient lighting, photovoltaics and energy storage. Overall, Asia is a specialist in innovating and exporting climate change mitigation technologies but there are significant regional disparities.
Keywords: Q42; Q43; Q54; Q56; 330; green growth; competitiveness; low-carbon innovation